Identification of Key Regulatory Pathways of Basidiocarp Formation in Pleurotus spp. Using Modeling, Simulation and System Biology Studies - Anupam Barh; Kanika Sharma; Pankaj Bhatt; Sudheer Kumar Annepu; Manoj Nath; Mahantesh Shirur; Babita Kumari; Kirti Kaundal; Shwet Kamal; Ved Parkash Sharma; Sachin Gupta; Annu Sharma; et al. (Journal of Fungi, 2022)
Pleurotus (Oyster mushroom) is an important cultivated edible mushroom across the world. It has several therapeutic effects as it contains various useful bio-molecules. The cultivation and crop management of these basidiomycete fungi depends on many extrinsic and intrinsic factors such as substrate composition, growing environment, enzymatic properties, and the genetic makeup, etc. Moreover, for efficient crop production, a comprehensive understanding of the fundamental properties viz. intrinsic–extrinsic factors and genotype-environment interaction analysis is required. The present study explores the basidiocarp formation biology in Pleurotus mushroom using an in silico response to the environmental factors and involvement of the major regulatory genes. The predictive model developed in this study indicates involvement of the key regulatory pathways in the pinhead to fruit body development process. Notably, the major regulatory pathways involved in the conversion of mycelium aggregation to pinhead formation and White Collar protein (PoWC1) binding flavin-chromophore (FAD) to activate respiratory enzymes. Overall, cell differentiation and higher expression of respiratory enzymes are the two important steps for basidiocarp formation. PoWC1 and pofst genes were participate in the structural changes process. Besides this, the PoWC1 gene is also involved in the respiratory requirement, while the OLYA6 gene is the triggering point of fruiting. The findings of the present study could be utilized to understand the detailed mechanism associated with the basidiocarp formation and to cultivate mushrooms at a sustainable level.